Does Endoplasmic Reticulum (ER) Stress Contribute to T-cell Exhaustion in B-ALL? - Kahrizi, Amir; Akbar, Armin; Najafi, Ahmad; Asgarian-Omran, Hossein; Karami, Hossein; Naderisorki, Mohammad; Karimi, Alireza; Tehrani, Mohsen (Iranian journal of immunology, 2025)
Glucose deprivation in T lymphocytes can trigger compensatory metabolic pathways, potentially contributing to T-cell exhaustion. Additionally, it may induce the unfolded protein response (UPR), ultimately resulting in endoplasmic reticulum (ER) stress. To examine the transcriptional profiles of endoplasmic reticulum (ER) stress markers and T-cell exhaustion indicators in CD8+ T lymphocytes isolated from B-ALL patients. Peripheral blood samples were collected from 22 untreated B-ALL patients and 22 healthy controls. Magnetic Activated Cell Sorting (MACS) was used to isolate CD8+ T lymphocytes. The relative gene expression was then assessed using qRT-PCR with primers specific to XBP1, CHOP, GLUT1, and T-bet. The ER stress response was significantly activated in CD8+ T lymphocytes from B-ALL patients, as evidenced by significant increase in both XBP1 and CHOP transcript levels, relative to normal donors. Although GLUT1 mRNA expression was significantly higher than in control groups, T-bet expression showed no significant difference between the two groups. Collectively, our gene expression data suggest ER stress activation in CD8+ T lymphocytes from B-ALL patients. These findings warrant further investigation into ER stress-related signaling pathways and their potential role in promoting T-cell exhaustion in B-ALL.